Henry E. Dosch, Director of Exhibits, Alaska Yukon Pacific Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
On verso of image: H.E. Dosch, Director of Exhibits PH Coll 727.826 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number